Menuju Akuntansi Cerdas: Literasi Digital untuk Talenta Muda di Era AI. - Munjirin, Munjirin; Andriani, Juwita (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to understand the experiences and perceptions of young talents regarding digital literacy in the era of artificial intelligence (AI), focusing on Accounting students at SMK Muhammadiyah Larangan Brebes. This research examines how accounting literacy, understanding of digital concepts, and learning interest interact to shape young generations’ readiness to face digital transformation in the accounting field. The study employs a descriptive qualitative method, with data collected through interviews, observations, and documentation. The data were analyzed using a thematic approach to identify patterns of understanding, learning behavior, and student motivation in utilizing AI-based technologies. The findings reveal that students possess a fairly good understanding of digital accounting literacy, although it remains limited to technical aspects. A deeper understanding of digital concepts has been shown to enhance students’ curiosity and learning motivation. Moreover, the integration of AI technology in the learning process fosters adaptive thinking and a positive attitude toward technological change. Teachers play an essential role in guiding students to comprehend both the function and ethics of AI use in professional accounting contexts.Overall, this study concludes that digital literacy is not merely related to technical skills but also encompasses cognitive and affective aspects that shape young talents’ preparedness in the AI era. Accounting literacy, digital concepts, and learning interest work synergistically to develop an adaptive, critical, and competitive young generation amid ongoing digital transformation